Sanditon. Season three [videorecording (DVD)] - Young, Justin (Screenwriter); Ainsworth, Joe; Gibb, Andrea; French, Robin; Bytheway, Colin; Spain, Joe; Williams, Rose, 1994-; Ashfield, Kate; Bolam, James, 1935-; Brigden, Cai; Clarke, Crystal (Actor); Convery, Turlough; et al. (PBS Distribution, 2023)
The final season continues the story of high-spirited heroine, Charlotte Heywood, and her friend, Georgiana Lambe. What adventures, scandals, intrigue and above all else - romance - await them?